The Ottoman postal and telegraph services in the last quarter of the nineteenth century - Okan, Ayşegül. (Thesis (M.A.)-Bogazici University. Atatürk Institute of Modern Turkish History, 2003., 2003)
Public postal services were inaugurated in the Ottoman Empire with the establishment of the Ministry of Post in 1840. The institute was an extension of the new administrative approach which appeared especially with the Tanzimat Decree.The first telegraph lines were installed in 1855, during the Crimean War. In time, the telegraphic network developed rapidly in the Empire. From 1871, the telegraph and postal services were managed from a single administrative center. This thesis tells of the modernization process seen in the Ottoman postal and telegraph services in the last quarter of the nineteenth century. The process, which was begun with the membership of the Ottoman State in the Universal Postal Union in 1874 and continued under the reign of Abdülhamid II, created quantitative and qualitative changes in post and telegraph services. The system began to work much more efficiently than it had in the past. Another important finding of the thesis is that the sultan was not the only actor in the process; officials placed in the low ranks of the bureaucratic structure played significant roles in this improvement.The thesis also examines the foreign post offices operating in the Empire. The state struggled with the foreign post offices to obtain its monopoly right over communication systems; although it did not reach certain results, the Ottomans did accomplish the modernization of their own system.The survey depends mostly on primary sources.
Keywords: Postal service -- Turkey -- History.; Telegraph -- Turkey -- History.